Elite athletes and parenthood - financial conditions, (support) structures and family planning - Hellborg, A. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
Elite athletes as parents have received greater attention in recent years, which has raised questions regarding the possibilities of combining an elite career with family life. Research in this area has increased during the 2000`s. Palmer and Leberman`s study (2009) of mothers found that balancing time between family and elite sports was difficult; this is also found in other studies (Andreasson et al, 2018). Time seems to be a key issue when committing to a sporting career and having children. The purpose of this study is to explore and analyse elite athletes` view of combining elite sports and parenthood from a financial and structural perspective. As analytical tools Mills ideas of personal troubles and public issues is relevant as well as theories surrounding parenthood and gender equality. An online survey directed to active elite athletes was used. The survey consisted of questions about financial conditions, support and the structuring of their sporting activities. I received 27 answers from athletes who had children and 11 from those who did not have children. The results show that about half of those who have children say that their financial situation has been worse since they had children. Two thirds do not feel they have support from their national association. There is a lack of support for bringing children to competitions, which was an expressed wish for some. About half of the respondents said that the association need more knowledge about combining elite sports and parenthood. Both groups have elite sporting colleagues that have had children during their career. Those who do not have children express that it will be important to try to plan when to have children, so it does not collide with important competitions. This is something that those who had children did not say to the same extent. The conclusion is that the associations are not offering support to the elite athletes, according to the athletes. The athletes wish there were more support to bring children to competitions but also for the association to show support for their situation. Some even expressed that the association were uninterested in their situation. The athletes` wish for support can be perceived as an opinion that combining elite sports with parenthood is a public issue that the association need to help them with. However, the lack of support they receive may be interpreted as a perception of this situation as a personal trouble that the athletes have to figure out for themselves (cf. Mills, 1971/2002). There may be a gap in the perception of this situation between athletes and the associations.